2019
DOI: 10.1080/1828051x.2018.1547127
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary globin, a natural emulsifier, on the growth performance and digestive efficiency of broiler chickens

Abstract: The feed utilisation of young chicks is characterised by a suboptimal fat digestibility, which can be improved by means of dietary emulsifiers. The objective of this study was to evaluate the effect of dietary Globin on the energy efficiency and digestibility of starter feeds and on the production performance of broilers throughout the whole rearing cycle. A total of 224-day-old ROSS 708 chickens (14 birds/pen, 8 replicates/treatment) were fed ad libitum with either a basal diet (C) or a basal diet with the ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 23 publications
1
14
2
Order By: Relevance
“…Therefore, numerous nutritional hypotheses might explain the different results observed between the standard ME and low-ME diets, such as enzymatic digestion of protein and nonstarch polysaccharides in soybean meal or more efficient emulsification and digestion of dietary oil. Although we do not present evidence in this article for any mode of action in the gastrointestinal tract, all these modes of action have been demonstrated to improve broiler chick performance ( Singh et al., 2017 , Dabbou et al., 2019 , Hosseindoust et al., 2019 ).…”
Section: Discussionmentioning
confidence: 75%
“…Therefore, numerous nutritional hypotheses might explain the different results observed between the standard ME and low-ME diets, such as enzymatic digestion of protein and nonstarch polysaccharides in soybean meal or more efficient emulsification and digestion of dietary oil. Although we do not present evidence in this article for any mode of action in the gastrointestinal tract, all these modes of action have been demonstrated to improve broiler chick performance ( Singh et al., 2017 , Dabbou et al., 2019 , Hosseindoust et al., 2019 ).…”
Section: Discussionmentioning
confidence: 75%
“…In a study conducted on broilers, the results of supplementation lysolecithin in feed showed no significant effect on the growth performance of the broilers for one to 21 days [20]. In a similar study, Dabbou et al [21] reported that supplementation with natural emulsifiers for one to 10 days significantly decreased the FCR in broilers, but there were no significant differences in BWG or FI. In contrast, a study by Bontempo et al [15] showed a significant improvement in average daily gain with the supplementation of synthetic emulsifier to the feed for one to 12 days and a significant decline in the FCR for 22 to 44 days.…”
Section: And Discussionmentioning
confidence: 93%
“…At 70 and 174 days old, excreta samples were collected from 36 pullets per dietary treatment, following the procedure described by Dabbou et al (2019) [25]. Briefly, birds were kept for 1 h in cages (3 birds of the same pen/cage).…”
Section: Excreta Sampling Dry Matter and Parasite Loadmentioning
confidence: 99%